2001
DOI: 10.1038/oby.2001.10
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Thermogenic Sympathetic Response to Food Intake between Obese and Non‐obese Young Women

Abstract: MATSUMOTO, TAMAKI, CHIEMI MIYAWAKI, HIDETOSHI UE, TOMO KANDA, YASUHIDE YOSHITAKE, AND TOSHIO MORITANI. Comparison of thermogenic sympathetic response to food intake between obese and non-obese young women. Obes Res. 2001;9:78 -85. Objective: Sympathetic nervous system abnormality in humans is still a matter of debate. The present study was designed to examine diet-induced autonomic nervous system activity and metabolic change in obese and non-obese young women. Research Methods and Procedures: Sixteen age-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
117
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(123 citation statements)
references
References 38 publications
(69 reference statements)
5
117
0
1
Order By: Relevance
“…29 As the sympathetic branch of the autonomic system particularly contributes to coordinating energy homeostasis, any alteration in sympathetic nervous system is widely assumed to promote onset and development of obesity. 14,30 Nagai et al 30 showed that the complete autonomic blockade evaluated by means of PSA of HRV significantly reduced the energy expenditure in humans. In addition, Heinonen et al 1 found that the Glu 9 /Glu 9 genotype was associated with reduced basal metabolic rate in obese Finns population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 As the sympathetic branch of the autonomic system particularly contributes to coordinating energy homeostasis, any alteration in sympathetic nervous system is widely assumed to promote onset and development of obesity. 14,30 Nagai et al 30 showed that the complete autonomic blockade evaluated by means of PSA of HRV significantly reduced the energy expenditure in humans. In addition, Heinonen et al 1 found that the Glu 9 /Glu 9 genotype was associated with reduced basal metabolic rate in obese Finns population.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] In the present study, we used HRV as a strategy to study the sympathetic and vagal controls during sustained handgrip exercise in obese individuals with 12Glu9 deletion polymorphism of the a 2B -AR gene. Previous investigations using HRV analysis [10][11][12][13][14] and measurements of plasma catecholamines 15,16 showed altered sympathetic responsiveness during cold exposure, spicy food containing capsaicin and glucose ingestion in obese individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Spraul et al 2 identified a role for reduced sympathetic nervous system activity in bodyweight gain, which increases susceptibility to obesity. Recent data has suggested that obese individuals exhibit significantly lower sympathetic nervous system activity in response to various physiological challenges, such as food intake 3 and capsaicin intake. 4 These results would suggest that overweight individuals might be treated effectively with the use of sympathomimetic agonists.…”
Section: Introductionmentioning
confidence: 99%
“…High-pass filtering at 0.007 Hz was chosen to include the frequency components associated with thermoregulatory control in SNS activity as identified by the Simplex method. 13 We previously reported that 0.007-0.035 Hz of the heart rate variability power spectrum was selectively increased against various thermogenic perturbations, such as acute cold exposure, 11,12 food intake, 13 high-carbohydrate meal 15 and spice-containing meal 14,16 in adult individuals [12][13][14] or children. 11,15,16 After passage through the Humming-type data window, power spectral analysis using a fast Fourier transform was performed on a consecutive 1024 s time series of R-R interval data obtained during the measurement.…”
Section: Calculation Of Thermoregulatory Sns Activitymentioning
confidence: 99%
“…To examine the role of UCP1 in usual energy balance in adult humans, we therefore investigated whether or not the -3826 A/G polymorphism of the UCP1 gene is associated with resting energy expenditure (REE) and thermoregulatory SNS activity by power spectral analysis of heart rate variability, according to our previously reported method, [11][12][13][14][15][16] in young healthy females.…”
Section: Introductionmentioning
confidence: 99%